Financial development, trade and growth triangle: the case of India - Katircioglu, Salih; Kahyalar, Neslihan; Benar, Hasret (Emerald Group Publishing Ltd, 2007)
Purpose - This paper aims to investigate the possible co-integration and the direction of causality between financial development, international trade and economic growth in India. Design/methodology/approach - Annual data covering the 1965-2004 period have been used to investigate co-integration and Granger causality tests between financial development, international trade, and growth after employing unit root tests to see if the variables under consideration are stationary. Findings - Results reveal that there is a long-run equilibrium relationship between financial development, international trade and real income growth in the case of India. Furthermore, unidirectional causality was investigated that runs from real income to exports and imports, from exports to imports, M2 and domestic credits, from M2 to imports, from imports to domestic credits. Bidirectional causality has also been obtained between real income and M2, and between real income and domestic credits. Finally, no direction of causality has been obtained between M2 and domestic credits. Research limitations/implications - Expanded data can be used for further comparison. Practical implications - This study has shown that the supply-leading and the demand-following hypotheses cannot be inferred for the Indian economy alone themselves. And furthermore, the export-led and the import-led hypotheses again cannot be inferred for the Indian economy based on the sample period, 1965-2004. Originality/value - This study is the first of its kind which investigates the possible co-integration and the direction of causality between the financial development, international trade and economic growth triangle not only in the case of India but also in the relevant literature to the best of one's knowledge.
Keywords: Financial management; Trade; Economic growth; India